2007
DOI: 10.1038/sj.jcbfm.9600378
|View full text |Cite
|
Sign up to set email alerts
|

Stroke-Evoked Angiogenesis Results in a Transient Population of Microvessels

Abstract: The role of angiogenesis after stroke is unclear; if angiogenesis supports long-term recovery of blood flow, then microvessel hyperdensity consequent to angiogenesis should persist in infarcted cortex. Here, we assess the long-term stability of ischemia-induced microvessels after 2-h transient rat middle cerebral artery occlusion (tMCAo) followed by 30, 90, or 165 days of reperfusion. Stereological measures of microvessel density were taken adjacent to and within cortical cysts. Vascular permeability was docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
61
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 49 publications
12
61
0
4
Order By: Relevance
“…With regard to the role of angiogenesis after cerebral ischemia, Yu et al [63] proposed that the major function of ischemia-stimulated vessel formation is to eliminate necrotic tissue and debris via macrophages. Wei et al [64] demonstrated that angiogenesis helps to restore blood flow in the ischemic zone by interacting with the arteriole collateral circulation established after cerebral ischemia, thereby improving the long-term recovery of neurological function in rats.…”
Section: Angiogenesis After Cerebral Ischemiamentioning
confidence: 99%
“…With regard to the role of angiogenesis after cerebral ischemia, Yu et al [63] proposed that the major function of ischemia-stimulated vessel formation is to eliminate necrotic tissue and debris via macrophages. Wei et al [64] demonstrated that angiogenesis helps to restore blood flow in the ischemic zone by interacting with the arteriole collateral circulation established after cerebral ischemia, thereby improving the long-term recovery of neurological function in rats.…”
Section: Angiogenesis After Cerebral Ischemiamentioning
confidence: 99%
“…Yet, CD14 high CD16 + monocytes could also be beneficial through its richer expression of proangiogenic Tie-2 (Murdoch et al, 2007) and their strong phagocytic activity (Skrzeczynska-Moncznik et al, 2008). Together, angiogenesis and phagocytosis could facilitate the clearance of injured brain tissue after stroke (Manoonkitiwongsa et al, 2001;Yu et al, 2007). The meaning of the high expression of TLR2 in this population remains to be further investigated.…”
Section: Figurementioning
confidence: 99%
“…In experimental ischemia, monocytes can promote inflammation, but they may also contribute to the resolution of inflammation (Manoonkitiwongsa et al, 2001;Yu et al, 2007). In patients with acute stroke, there is a significant increase in the number of circulating monocytes, and this increment is particularly conspicuous in patients who experience a stroke-associated infection (SAI) .…”
Section: Introductionmentioning
confidence: 99%
“…Stroke opens the BBB in peri-infarct cortex for up to 90 d after infarction (Veltkamp et al, 2005;Yu et al, 2006). To establish BBB permeability in this stroke model, SDF1␤, Ang1, and a function-blocking anti-Tie2 antibody were labeled by fluorescent conjugation and delivered systemically for 5 d after stroke.…”
Section: Gain-and Loss-of-function Within the Neurovascular Nichementioning
confidence: 99%